Por uma história social de medos e resistências: inquisição e sociedade no Brasil colonial (séc. XVI-XVIII) - Oliveira, Halyson Rodrygo Silva de (2022)
This doctoral thesis investigates, from the point of view of social history, the reactions to the so-called ‘pedagogy of fear’ in the context of the inquisitorial visits taken place in Brazil between the 16th and 18th centuries. The main objective of this research is to demonstrate the existence of different ways to resist the intimidation devices used by the Holy Office of the Inquisition. The set of documents analyzed in this work consisted of printed sources and handwritten documents in the custody of the National Archives of Torre do Tombo, in the city of Lisbon, Portugal. Books of denunciations and confessions of visitations were used as main resource, as well as criminal processes arising from these meticulous investigation of consciences. In addition to these documents, other sources were used in the research, such as, for example, Regiments of the Holy Office, dictionaries and political treaties of the period. From the laborious dialogue between qualitative methods and the survey of quantitative indices, the power relations between the inquisitorial court and colonial society were analyzed. Among the results achieved, one can see the identification of several arrangements developed by the individuals under inspection, such as, for example, strategies and tactics for maintaining prohibited religious habits, as is the case of Judaism practiced occultly; the self-preservation of physical and material life; the defense of the memory of the sentenced defendants; the popular insults against the Holy Office and its local representatives, as well as the questioning of the methods and procedures of the Inquisition, which culminated in the progressive discontinuity of the ‘pedagogy of fear’ in the context of the second half of the 18th century. The dialogical relationships between fear and social resistance show, in this sense, a history of struggles, convictions, notions of the world and interests that guided multiple relationships of different individuals and social groups among themselves and with the Portuguese Holy Office in colonial Brazil.